• Support PF! Buy your school textbooks, materials and every day products Here!

Geometric Sum

  • Thread starter Moridin
  • Start date
  • #1
664
3

Homework Statement



Calculate the following sum:

[tex]\sum_{k=1}^{10} 3 \cdot 2^{k}[/tex]

The Attempt at a Solution



[tex]\sum_{k=1}^{10} 3 \cdot 2^{k} = 3 \cdot \sum_{k=1}^{10} 2^{k} = 3 \cdot (2^{10} - 1)[/tex]

Although it seems that I am missing something.
 

Answers and Replies

  • #2
D H
Staff Emeritus
Science Advisor
Insights Author
15,393
682
[tex]\sum_{k=1}^{10} 3 \cdot 2^{k} = 3 \cdot \sum_{k=1}^{10} 2^{k} = 3 \cdot (2^{10} - 1)[/tex]

Although it seems that I am missing something.
Very close but no cigar. How can [itex]\sum_{k=1}^{10} 2^{k} = 2^{10} - 1[/itex]? You are missing something from the right-hand side.
 
  • #3
664
3
Right, if you divide a term in the sum by the previous term, you get 2, not 1? So a factor of 2 is missing.
 
  • #4
Gib Z
Homework Helper
3,346
4
Do you know [tex]x^n - y^n = (x-y)(x^{n-1} + x^{n-1}y + ... + y^{n-1} )[/tex] ?

For (x,y) = (2,1) that forms into what you need. Look at the expansion of what you have, 2^10 - 1, and see how that falls different to the sum you want on the RHS, then change it accordingly =]
 
  • #5
**Edited by user.
 
Last edited:
  • #6
Gib Z
Homework Helper
3,346
4
Forum regulations prohibit giving out answers to homework threads - please just give hints. Edit your post.
 
  • #7
ok sorry buddy!

@author of thread... look up summation of a GP
 
  • #8
HallsofIvy
Science Advisor
Homework Helper
41,772
911

Homework Statement



Calculate the following sum:

[tex]\sum_{k=1}^{10} 3 \cdot 2^{k}[/tex]

The Attempt at a Solution



[tex]\sum_{k=1}^{10} 3 \cdot 2^{k} = 3 \cdot \sum_{k=1}^{10} 2^{k} = 3 \cdot (2^{10} - 1)[/tex]

Although it seems that I am missing something.
The formula you are trying to remember is
[tex]\sum_{k=0}^n a r^k= a\frac{1-r^{n+1}}{1- r}[/itex]
For r= 2, so that 1-r= 1-2= -1, that becomes
[tex]\sum_{k=0}^n a 2^k= a (2^{n+1}- 1)[/tex]

There are two important differences between that and the formula you are using.
 
  • #9
664
3
Let's see.

The general formula is

[tex]\sum_{k=0}^n a r^k= a\frac{1-r^{n+1}}{1- r}[/tex]

Now the terms in the sum

[tex]\sum_{k=1}^{10} 3 \cdot 2^{k} = 6 + 12 + 24 + ... + 3072[/tex]

This means that

n = 9 (10-1)
r = 2 (taking the n:th term/(n-1):th term)
a = 6 (the starting term)

So

[tex]\sum_{k=1}^{10} 3 \cdot 2^{k} = 6\frac{1-2^{9+1}}{1-2} = 6\frac{1-2^{10}}{1- 2} = 6(2^{10} - 1)[/tex]

That sounds about right?

Why is n = 9 here? Is that just the number of terms that have an exponent >= 2?
 
  • #10
Someone above told me not to give out the answer.. and btw your answer is correct.. and yes n = 10 not 9 . There are 10 terms of the GP.
 
  • #11
HallsofIvy
Science Advisor
Homework Helper
41,772
911
spdeyunlimit, n= 9, not 10 because because the sum starts with k= 1. He is thinking of this as 6+ 6(2)+ 6(22)+ 6(2n) with n running from 0 to 9.

Another way to do the problem would be to use the same formula with n= 10, a= 3, but then subtract off 3- to allow for the missing 3(20) term.
 
  • #12
for the GP
a, ar, ar^2, ar^3 ... and so on
Sum of first n terms = a(1 - r^n) / (1-r)
where in the first term the power of r is 0.. whereas here it is one.. so yeah i got that.. it will be for n = 9
 

Related Threads for: Geometric Sum

  • Last Post
Replies
4
Views
2K
Replies
10
Views
1K
Replies
8
Views
728
Replies
13
Views
5K
Replies
8
Views
1K
Replies
5
Views
2K
Replies
2
Views
4K
Replies
4
Views
2K
Top